THE SCIENCE LITERACY MEASUREMENT DESIGN ON THE QUALITY OF BIOLOGY LEARNING - anggis, eka (Jurnal Penjaminan Mutu, 2025)
Abstract Scientific literacy is one of the skills needed in the 21st century, especially to ensure mutual learning of biology. The aim of the research is to describe the design of measuring scientific literacy in biology learning. The research method used R & D Thiagarajan 4D (Define, Design, Develop and Disseminate). The instrument used is a material expert validation sheet and biology learning methodology. The results showed that there was 85.6% feasibility by material experts, 96% by learning methodology experts. The conclusion of the research is that the feasibility of a scientific literacy instrument in biology learning has been produced so that it can be used as a measuring tool to evaluate the quality of biology students' scientific literacy.